Numerical Integration of Functions Given by Data Points - Fejzić, Hajrudin (Sarajevo Journal of Mathematics, 2024)
Let a... 2000 Mathematics Subject Classification. Primary 26A06, 26A24, 41A44; Secondary 26D07, 26D15, 26D20